2016
DOI: 10.20937/rica.2016.32.04.10
|View full text |Cite
|
Sign up to set email alerts
|

Produced Waters of the Oil Industry as an Alternative Water Source for Food Production

Abstract: Increased water demand for crop irrigation requires new water sources in the short term. One alternative may be unconventional ground water sources, such as produced waters that are pumped to the surface mixed with hydrocarbons in the process of drilling when extracted gas or oil. Such produced waters are confined to unproductive wells or used to maintain pressure in petroleum deposits. However, previous studies have highlighted the possibility of using these waters within the industrial sector as well as in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…In California, the oil firm Chevron supplies Cawelo Water District with 44 million m 3 of treated PW which is then blended with fresh water to irrigate18,600 ha of food crops (Arnold et al, 2004;Heberger and Donnelly, 2015;Martel-Valles et al, 2016). Another study in the Powder River Basin (USA) showed that PW is suitable for irrigation when mixed with fresh water in 1:3 ratio (Burkhardt et al, 2015).…”
Section: Adapting Produced Water To Irrigationmentioning
confidence: 99%
“…In California, the oil firm Chevron supplies Cawelo Water District with 44 million m 3 of treated PW which is then blended with fresh water to irrigate18,600 ha of food crops (Arnold et al, 2004;Heberger and Donnelly, 2015;Martel-Valles et al, 2016). Another study in the Powder River Basin (USA) showed that PW is suitable for irrigation when mixed with fresh water in 1:3 ratio (Burkhardt et al, 2015).…”
Section: Adapting Produced Water To Irrigationmentioning
confidence: 99%
“…Current guidelines for agricultural water reuse require TDS concentrations to be <500 mg L -1 (Doran and Leong 2000;Ganesh and Lelong 2005;Beltran and Koo-Oshima 2006). Although certain crops can tolerate TDS levels up to 2000 mg L -1 , water with salinity above the threshold for irrigation may cause long-term soil salinity and fertility problems after infiltration and subsequent evapotranspiration, long after the practice has ceased (Martel-Valles et al 2016). This is particularly important for shallow soils in arid or semiarid climates, where excess salinity could irreparably damage fertility (Tanji and Kielen 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Wastewater (produced water) is a byproduct of oil and natural gas extraction industry, originated in the formations holding oil and gas or from the water previously injected for oil and gas extraction (Clark and Veil, 2009;Martel-Valles et al, 2016). Physicochemical composition of the produced water varies considerably according to the geographic location, the geologic formation, the type of hydrocarbon and the lifetime of a reservoir (Clark and Veil, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Physicochemical composition of the produced water varies considerably according to the geographic location, the geologic formation, the type of hydrocarbon and the lifetime of a reservoir (Clark and Veil, 2009). Produced water with high salinity can reach until f ive or six times the total dissolved solids of seawater (Martel-Valles et al, 2016). According to Mexican Off icial Standard NOM-143- SEMARNAT-2003SEMARNAT- (2005 and (Martel-Valles et al, 2013, wastewater contains compounds of low molecular weight, such as BTEX (benzene, toluene, etilbenzene, xylene), organic acids, condensates, oils, fats, polycyclic aromatic hydrocarbons (PAHs), and phenols.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation